Assessment of rainwater runoff using the Rational Method and its applications - Applied to rural case studies in Ockelbo, Sweden, affected by the extreme rain event in Gävleborg county of August 2021 - Dristig, Annie; Välikangas, Elin (My University, 2022)
The aim of this master thesis is to investigate different applications of the Rational Method (RM), applied to manually calculate rainwater runoff and estimate culvert pipe dimensions at two rural case study areas affected by the extreme rainfall in Gävleborg county in August 2021. This rain event is in Sweden referred to as Gävleregnet. Each case study consisted of a culvert pipe transporting a creek through a country road. The dimensioning flows from the forested catchment areas were calculated by the RM and three of its applications; the version of Svenskt Vatten (SV-RM), the Swedish Transport Administration (STA-RM) and Flödesappen. All of these except the latter, which is a digital modelling tool, were combined with the Time-area Method (T-A), and their calculations were based on two rain scenarios; the Worst Case of Intensity (WCI) and the Worst Case of Return Period (WCRP). All four applications of the RM utilized Colebrook’s method to determine the suitable pipe dimensions needed to manage the dimensioning flows. Furthermore, the catchment areas and calculations for RM, SV-RM and STA-RM were estimated manually in Excel and GIS. A field visit was also conducted to retrieve deepened information of the case study areas. The results of the areal parameters were compared between the digital calculation in Flödesappen and the manual methods. The influence of some parameters on the peak flow was investigated in a Sensitivity Analysis (SA) for each method and rain scenario. Overall, the results showed that the WCRP was the actual worst of the two scenarios, for both case studies, where the highest peak flows were generated by the two methods that considered a climate factor (SV-RM and STA-RM). The results from the SA show that the most affected flow is generated by the change of the catchment area in the WCRP scenario for SV-RM and STA-RM.
Keywords: Rational Method; Time-area method; Culvert pipe; Runoff; Swedish Transport Administration; Svenskt Vatten; Gävleregnet; Extreme rain event; Rural; Catchment area